2002
DOI: 10.1063/1.1497708
|View full text |Cite
|
Sign up to set email alerts
|

From amplified spontaneous emission to microring lasing using nanocrystal quantum dot solids

Abstract: We study different emission regimes in close-packed films of chemically synthesized CdSe nanoparticles [nanocrystal quantum dots (NQDs)]. We observe that the NQD photoluminescence is dominated by excitons and biexcitons, respectively, before and after the threshold for stimulated emission. Furthermore, we demonstrate the regime of microring lasing into sharp, whispering-gallery modes using NQD solids incorporated into microcapillary tubes. This result indicates a feasibility of miniature, solid-state laser dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
234
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(245 citation statements)
references
References 13 publications
9
234
0
2
Order By: Relevance
“…S4 †). In addition, although NR 6 has the longest CdS rod length, we achieved almost the same amount ($8 nm) of blue-shied ASE from NR 6 when compared to NR 5 . It is also shown that both NR 5 and NR 6 have the same radiative lifetime, which conrms that photoluminescence lifetimes are a good indicator of connement.…”
mentioning
confidence: 70%
“…S4 †). In addition, although NR 6 has the longest CdS rod length, we achieved almost the same amount ($8 nm) of blue-shied ASE from NR 6 when compared to NR 5 . It is also shown that both NR 5 and NR 6 have the same radiative lifetime, which conrms that photoluminescence lifetimes are a good indicator of connement.…”
mentioning
confidence: 70%
“…A linear fi t was used to account for the change in PL intensity as a function of excitation stripe length prior to optical amplifi cation [ 4 ] while the onset and subsequent saturation of the ASE intensity was fi tted with a previously reported 1-D amplifi er model: [ 6 , 15 ] I ∝ e gla 1 − e −(z−z 0 ) la used to explicate the absence and presence of ASE in short and long CdSe seeded CdS nanorods respectively, [ 21 ] given that in our case the dimensions of the CdS arms in both small and large core tetrapods as well as their volume fractions in the fi lm are comparable. One plausible explanation would be to consider an exciton blocking effect in which the small CdSe core is populated with a high density of excitons at suffi ciently large excitation intensities such that the electrons and holes photogenerated in CdS do not experience a strong driving force for relaxing into the CdSe core, thus recombining radiatively.…”
Section: Doi: 101002/adma201200121mentioning
confidence: 99%
“…1 These particles cover the visible to near-infrared spectral range and have important potential applications in biology and electro-optical devices. [2][3][4][5][6][7] Such electro-optic devices rely on the conversion of light into excited electrons and holes (excitons) and vice versa, and knowledge of the processes immediately following photoexcitation is therefore essential for these applications, in addition to the fundamental interest in exciton and charge dynamics in QDs.…”
Section: Introductionmentioning
confidence: 99%